Oviposition choices of the willow sawfly nematus oligospilus is affected by conspecific herbivory in the native willow salix humboldtiana. - Valladares, Gabriela Alejandra (2016)
Most herbivorous insects start attacking a plant by laying eggs on it. Host plant selection can be crucial for the survival of the new insect generation, especially when larvae lack mobility to select their own feeding places. The willow sawfly, Nematus oligospilus (Förster), is an exotic emerging pest in Salix commercial forests and has been reported worldwide. Females of this species are parthenogenetic in the southern hemisphere and must find and recognize their host plant when they emerge as adults.The objective of the present work was to evaluate the effect of conspecific herbivory on the oviposition choices of N. oligospilus females. Local and systemic effect, were studied. First, choice tests were conducted on Salix humboldtiana (Willdenow) and S. babylonica (Linneaus) var. sacramenta in undamaged potted plants vs. plants after 48 hs. of larval feeding. Results on S. humboldtiana, suggests strong repellence to plants with damage as females highly preferred branches from undamaged plants for oviposition. This was observed for both, local and systemic damage. For S. babylonica we did not find significant differences between treatments.In order to look for the chemical cues associated to this behavior, plant volatiles are being analyzed. Preliminary observations showed qualitative differences between the chemical composition of damaged and undamaged plants, suggesting the presence of plant cues elicited by larval feeding as oviposition repellents.